2022
DOI: 10.1097/iop.0000000000002292
|View full text |Cite|
|
Sign up to set email alerts
|

Müller Muscle Conjunctival Resection: A Multicentered Prospective Analysis of Surgical Success

Abstract: Symmetry success defined as a patient achieving an intereyelid MRD1 difference ≤1 mm at the 3-month postoperative visit. *Significant predictor of symmetry success on bivariate analysis.†Variable previously considered relevant to symmetry success. B, beta coefficient; MRD1, marginal reflex distance-1; SE, standard error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Authors of some studies hypothesize that phenylephrine administration simulates the postoperative result and propose a resection algorithm based on the phenylephrine response. 13 , 18 , 24 , 25 , 28 , 29 , 33 In contrast, other studies have obtained excellent results after performing mullerectomy in eyelids that were unresponsive to phenylephrine 12 , 27 or in patients with Horner syndrome. 14 In a recent prospective study by Lueng et al, the MRD1 measured after fenyl drops did not predict postoperative success, in contrast to the prefenyl MRD1, which was the only significant predicting factor for success.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Authors of some studies hypothesize that phenylephrine administration simulates the postoperative result and propose a resection algorithm based on the phenylephrine response. 13 , 18 , 24 , 25 , 28 , 29 , 33 In contrast, other studies have obtained excellent results after performing mullerectomy in eyelids that were unresponsive to phenylephrine 12 , 27 or in patients with Horner syndrome. 14 In a recent prospective study by Lueng et al, the MRD1 measured after fenyl drops did not predict postoperative success, in contrast to the prefenyl MRD1, which was the only significant predicting factor for success.…”
Section: Discussionmentioning
confidence: 93%
“… 14 In a recent prospective study by Lueng et al, the MRD1 measured after fenyl drops did not predict postoperative success, in contrast to the prefenyl MRD1, which was the only significant predicting factor for success. 33 In our opinion, the preoperative phenylephrine administration test to determine whether the patient with eyelid ptosis is a candidate for the MMCR procedure and to estimate resection margins can be omitted. The success of the MMCR procedure is likely not determined by the exact amount of muscle resection, but more likely by general posterior lamellar shortening resulting in a levator aponeurosis plication (either shortening or reinserting onto the tarsus) 26 , 34 , 35 ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies conducted to evaluate the MMCR surgery outcome, however, the MRD1 analyze method was not mentioned. For example, Leung et al has conducted a multicenter prospective study and evaluated the effect of 2.5% phenylephrine test, amount of the response to the phenylephrine test and excised MMC tissue on the surgical success rate of the MMCR surgery, however, the measurement method was not stated in the paper (18). Similarly, Dryden et al reported the results of the levator-Muller tissue complex resection (the technique described by Morris et al) surgery for ptosis repair by measuring the MRD1 and stated that, in cases who responded to the phenylephrine test can benefit from the 8 mm and 10 mm resection of the levator-Muller tissue complex, however, the authors did not mention about the MRD1 measurement method in the paper (7).…”
Section: Discussionmentioning
confidence: 99%
“…The first group comprised subjects who underwent ELA and the second group were patients who underwent MMCR for the management of involutional eyelid ptosis with levator function greater than 10 mm. Unilateral ptosis was defined as MRD1 ≤2.0 mm and more than a 1 mm difference in MRD1 between two eyelids (14) .…”
Section: Methodsmentioning
confidence: 99%